Utilizing Children's Literature-Based Ecoprenuership as Learning Content for Financial Literacy in Primary Schools - Susan R Bahara; Naniek Jusnita; Sri Ayu; Manda; Mughira (Universitas Islam Negeri Palopo, 2025)
This research aims to examine the content of financial literacy in language and literature learning and to provide a conceptual and contextual description of the use of children's literature-based ecopreneurship as an effort to improve financial literacy skills from an early age. The implementation of this research involved one elementary school (SD) Negeri 44 Kota Ternate that has implemented several incidental programmes related to the concept of ecoprenuership and financial literacy. The curriculum used is the 2013 curriculum. The method used in this research is through interviews with teachers, students, classroom observations and analysis of language and literature learning content through thematic textbooks. The results of the analysis explained that the content of financial literacy in the concept of ecopreunership contained in thematic textbooks for elementary schools (SD) grade II and V is an effort of educators and the government to provide entrepreneurship-based financial education and the environment to students covering the domains of linguistics, psychology and pedagogics (education science) integrated in the ultimate goal of language learning, namely students have qualified language skills. The information, knowledge and insights on finance and entrepreneurship provided in reading textbooks have a positive impact on attitudes of responsibility, frugal living, innovation, and more accurate, precise and regular planning for the future in organising financial planning.